The Epigenetic Landscape of Acute Myeloid Leukemia - Conway O'Brien, Emma (Hindawi Publishing Corporation, 2014)
Acute myeloid leukemia (AML) is a genetically heterogeneous disease. Certain cytogenetic and molecular genetic mutations are recognized to have an impact on prognosis, leading to their inclusion in some prognostic stratification systems. Recently, the advent of high-throughput whole genome or exome sequencing has led to the identification of several novel recurrent mutations in AML, a number of which have been found to involve genes concerned with epigenetic regulation. These genes include in particular DNMT3A, TET2, and IDH1/2, involved with regulation of DNA methylation, and EZH2 and ASXL-1, which are implicated in regulation of histones. However, the precise mechanisms linking these genes to AML pathogenesis have yet to be fully elucidated as has their respective prognostic relevance. As massively parallel DNA sequencing becomes increasingly accessible for patients, there is a need for clarification of the clinical implications of these mutations. This review examines the literature surrounding the biology of these epigenetic modifying genes with regard to leukemogenesis and their clinical and prognostic relevance in AML when mutated.